Permeability of Hydrate-Bearing Sediment Formed from CO2-N2 Mixture - Nan Li; Ziyang Fan; Haoran Ma; Shuai Jia; Jingyu Kan; Changyu Sun; Shun Liu (Journal of Marine Science and Engineering, 2023)
CO2-N2-mixture injection can be used for the exploitation and reformation of natural gas hydrate reservoirs. The permeability evolution of sediments in the presence of CO2-N2 hydrate is very important. In current permeability tests, hydrate-bearing sediment formed from CO2-N2 gas mixture is rarely involved. In this work, hydrate-bearing sediment was formed from CO2-N2 mixtures, and a constant flow method was employed to measure the permeability of the hydrate-bearing sediments. The effects of CO2 mole fraction and hydrate saturation on the permeability were investigated. The results show that gas composition is the key factor affecting hydrate formation. Hydrate saturation increases with increasing CO2 mole fraction in the gas mixture. The presence of hydrate formed from a CO2-N2 mixture leads to a sharp permeability reduction. The higher the fraction of CO2 in the injected gas mixture, the lower the sediment’s permeability. Our measured permeability data were also compared with and fitted to prediction models. The pore-filling model underestimates the permeability of hydrate-bearing sediments formed from a CO2-N2 gas mixture. The fitted hydrate saturation index in the Masuda model is 15.35, slightly higher than the general values, which means that the formed hydrates tend to occupy the pore center, and even block the pore throat.